Clinical efficacy of atezolizumab plus bevacizumab and chemotherapy in KRAS-mutated non-small cell lung cancer with STK11, KEAP1, or TP53 comutations: subgroup results from the phase III IMpower150 trial. Issue 2 (21st February 2022) - West, Howard Jack; McCleland, Mark; Cappuzzo, Federico; Reck, Martin; Mok, Tony SK; Jotte, Robert M; Nishio, Makoto; Kim, Eugene; Morris, Stefanie; Zou, Wei; Shames, David; Das Thakur, Meghna; et al.
Abstract : Background: The efficacy of atezolizumab (A) and/or bevacizumab (B) with carboplatin/paclitaxel (CP) chemotherapy was explored in the phase III, randomized IMpower150 study in patients with non-squamous non-small cell lung cancer (NSCLC) according to KRAS mutations (m KRAS ) and co-occurring STK11, KEAP1, or TP53 mutations. Methods: Mutation status was determined by circulating tumor DNA next-generation sequencing. Overall survival (OS) and progression-free survival (PFS) were analyzed in a mutation-evaluable intention-to-treat population (MEP; n=920) and SP263 (programmed cell death ligand 1 (PD-L1)) biomarker-evaluable population (n=774). Results: Within the m KRAS population (24.5% of MEP), ABCP showed numerical improvements vs BCP in median OS (19.8 vs 9.9 months; HR 0.50; 95% CI 0.34 to 0.72) and PFS (8.1 vs 5.8 months; HR 0.42; 95% CI 0.29 to 0.61)—greater than with ACP (OS: 11.7 vs 9.9 months; HR 0.63; 95% CI 0.43 to 0.91; PFS: 4.8 vs 5.8 months; HR 0.80; 95% CI 0.56 to 1.13) vs BCP. Across PD-L1 subgroups in m KRAS patients, OS and PFS were longer with ABCP vs BCP, but OS with ACP was similar to BCP in PD-L1-low and PD-L1-negative subgroups. Conversely, in KRAS -WT patients, OS was longer with ACP than with ABCP or BCP across PD-L1 subgroups. KRAS was frequently comutated with STK11, KEAP1, and TP53 ; these subgroups conferred different prognostic outcomes. Within the m KRAS population, STK11 and/or KEAP1 mutations were associated with inferior OS and PFS across treatments compared with STK11 -WT and/or KEAP 1-WT. In m KRAS patients with co-occurring m STK11 and/or m KEAP1 (44.9%) or m TP53 (49.3%), survival was longer with ABCP than with ACP or BCP. Conclusions: These analyses support previous findings of mutation of STK11 and/or KEAP1 as poor prognostic indicators. While clinical efficacy favored ABCP and ACP vs BCP in these mutational subgroups, survival benefits were greater in the m KRAS and KEAP1 -WT and STK11 -WT population vs m KRAS and m KEAP1 and m STK11 population, suggesting both prognostic and predictive effects. Overall, these results suggest that atezolizumab combined with bevacizumab and chemotherapy is an efficacious first-line treatment in metastatic NSCLC subgroups with m KRAS and co-occurring STK11 and/or KEAP1 or TP53 mutations and/or high PD-L1 expression.